Coccidia Species and Geographical Distribution in Genus Sus: A Scoping Review - Hongyu Han; Hui Dong; Qiping Zhao; Shunhai Zhu; Bing Huang (Microorganisms)
Swine coccidiosis is a widespread disease caused by species of the apicomplexan parasites Eimeria and Cystoisospora. Coccidiosis is a common cause of diarrhea in suckling piglets worldwide that directly reduces piglets’ immunity and increases the risk of infection with other enteropathogens, leading to increased clinical infection and mortality and consequent economic losses in the global pig industry. We searched the available literature to date, including English and Chinese articles, using six electronic bibliographic databases, including PubMed, ScienceDirect, Web of Science, CNKI, VIP Chinese Journal Database, and Wanfang Data. A standard approach for conducting scoping reviews was used to identify studies on the species and distribution of genus Sus coccidia worldwide. A quality assessment was done for each study reviewed and relevant information reported in the identified studies was collated, categorized, and summarized. A total of 149 publications and references were eligible for the final review. The distribution of 18 species of genus Sus coccidia recorded in 63 countries was collated. These included 15 Eimeria and 3 Cystoisospora species. C. suis was found in 48 countries, E. debliecki in 45 countries, E. scabra in 33 countries, E. polita in 31 countries, E. suis in 28 countries, E. perminuta in 26 countries, E. porci in 24 countries, E. neodebliecki and E.spinosa in 21 countries each, E.guevarai in 5 countries, C. almataensis in 4 countries, E. betica in 2 countries, and E. almataensis, E. ibrahimovae, E. residualis, E. szechuanensis, E. yanglingensis, and C. sundarbanensis were each found in only 1 country. Each species was listed according to its scientific name, host name, finding location, and geographical distribution. This review reflects the distribution and infection of genus Sus coccidia worldwide and provides more complete basic information to aid our understanding of the species and geographical distribution of coccidia in the genus Sus.